The harm resulting from enjoying a legally guaranteed right: (maternity leave as an example) - Murad, Dalal (Journal of the College of Education for Girls for Humanities, 2026)
The right to work is one of the rights guaranteed by the Constitution and stipulated by the legislator. Women went out alongside men to exercise their right to work and participated in all fields of life to contribute to meeting the daily needs of the family and to reduce the burden placed on men in providing the necessities for a decent living. Because of the woman’s privacy, the fact that she is a mother and a wife at the same time, and the need of her children and family to build a cohesive family and a healthy social environment, the legislator has allocated her certain leaves to the exclusion of men, such as pregnancy, childbirth, and maternity leave to fully exercise her role within her family. This type of leave is stipulated in the Constitution and the law, considering it a legally guaranteed right that cannot be infringed. However, stipulating maternity leave as currently applied may result in harm to the employee’s mother and conflict with it being a right that she must enjoy without resulting in any harm. This raises the responsibility of the legislator to pay attention to this issue and reconsider this stipulated right to mitigate or eliminate harm.